Targeted Temperature Management in Spontaneous Intracerebral Hemorrhage: A Systematic Review - Fischer, Marlene; Schiefecker, Alois; Lackner, Peter; Frank, Florian; Helbok, Raimund; Beer, Ronny; Pfausler, Bettina; Schmutzhard, Erich; Broessner, Gregor (Current Drug Targets, 2017)
Background: Fever is common in neurocritical care patients and is associated with poor outcome. Targeted temperature management (TTM), i.e. therapeutic hypothermia or controlled normothermia, after acute brain injury has been studied as a neuroprotectant for several decades. In contrast to pharmacological agents with specific targets TTM affects multiple pathophysiological mechanisms and is primarily thought to attenuate secondary brain injury. Most promising results have been obtained from experimental studies on cerebral ischemia or traumatic brain injury showing beneficial effects of hypothermia on structural and functional outcome. Objective: The aim of this systematic review of the literature is to provide an overview on preclinical and clinical data on the use of TTM for intracerebral hemorrhage (ICH). The impact of TTM on structural changes and functional outcome after induced and spontaneous ICH will be summarized. Results and Discussion: A positive influence of hypothermia has been observed in animal models of spontaneous ICH improving, among others, perihematomal edema, blood-brain barrier integrity, inflammation and thrombin-induced injury. However, results regarding functional outcome are conflicting. Little data is available on the effect of TTM after spontaneous ICH in humans. Single-center observational studies have shown reduced perihematomal edema under mild hypothermia and an association with favorable outcome. However, these beneficial effects on mortality and functional outcome have not been confirmed in randomized studies so far. Thus, results from ongoing, prospective randomized-controlled trials are highly anticipated.
Keywords: perihematomal edema